Keluarga Sebagai Preventif Radikalisme Dalam Diskriminasi Hak Beragama Perspektif Sad Dzari’ah Dan Islam Nusantara - Raya Hidayat; Kasuwi Saiban; Tutik Hamidah (Yayasan Cendekia Gagayunan Indonesia, 2025)
Indonesia faces several issues regarding the discrimination of religious worship rights, which clearly violates the regulations in Indonesia. In many cases of religious discrimination in the country, the neutrality of the government as a public servant is often called into question. Consequently, our society still lacks a proper understanding of religious tolerance. Instilling an understanding of appropriate solutions within families related to the discrimination of worship rights in Indonesia must be addressed more seriously. This study is essential to analyze radicalism in the discrimination of worship rights through the lens of sad dzari’ah. Furthermore, the researcher will examine the role of families in preventing worship rights discrimination from the perspective of Islam Nusantara. This research employs a qualitative approach based on library research. The findings indicate that discrimination against worship rights is inconsistent with sad dzari’ah because it can lead to significant harm, such as division and conflict. Therefore, worship rights discrimination must be prevented to align with the principles of sad dzari’ah. Additionally, strengthening family resilience through the cultivation of Islam Nusantara values can serve as a preventive effort against radicalism in worship rights discrimination.